An inhouse code for simulating heat recovery from boilers to heat water. (15th August 2018) - Ramadan, Mohamad; Khaled, Mahmoud; Haddad, Ahmad; Abdulhay, Bakri; Durrant, Andy; El Hage, Hicham
Abstract: The current tendency in energy domain is to reduce fuel consumption in favor of sustainable energy approaches. In this frame, the present work suggests an efficient way of heat recovery from boilers using concentric tube. The motivation behind the suggested concept is that it could be considered the cheapest, easiest to construct and simplest to use among all the existing heat recovery systems. In other words, the goal is to suggest a technique that could be utilized by a wider range of users regardless their technical level. Another advantage of the proposed concept is that is can be applied even on small scale boilers. With this in mind, a numerical tool is also developed allowing to make pre-studies to optimize the geometric parameters such as diameters and length, as well as to perform post-studies that allows to optimize operational parameters such as flow rates and fluids configurations. Furthermore, an experimental study is carried-out to validate the numerical results of the adopted heat exchanger. It was shown that water can be heated up to 100 °C depending on the flow rate and that the recovered heat increases through a rational function.